Effect of melatonin on insomnia and daytime sleepiness, in patients with obstructive sleep apnea and insomnia (COMISA): A randomized double-blinded placebo-controlled trial - Tahereh Madani Motlaq; Besharat Rahimi; Shahideh Amini (BMC, 2024)
Abstract Background COMISA is a common disorder that results in nighttime awakenings ,daytime sleepiness and PAP intolerance. Cognitive behavioral therapy for insomnia is used to improve PAP adherence and no medication has been evaluated in such population yet. Melatonin with its chronobiotic and antioxidant effects may have potential benefits on COMISA consequences at the appropriate dose and time. This study aimed to evaluate the effect of melatonin on sleep quality, daytime sleepiness and PAP Compliance in patients with COMISA. Methods This double-blind placebo trial randomly assigned eligible OSA patients who suffered from insomnia despite using PAP for over a month to receive either melatonin 10 mg or placebo. The primary outcomes were measured by changes in the Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESS), and Functional Outcomes of Sleep Questionnaire (FOSQ-10) over one month. Adherence to PAP was measured by the results of the PAP device reports on the average length of time and number of nights that the device was used. Results Thirty patients were enrolled in the study after randomization. The melatonin arm showed significant improvement in all four primary outcomes compared to the placebo arm. The PSQI score was 3.836±1.839 in the melatonin arm versus 10.522±3.626 in the placebo arm (Pvalue<0.001). The ISI score was 8.476±3.568 in the melatonin arm versus 14.47±4.50 in the placebo arm (Pvalue<0.001). The ESS score was 6.854±4.334 in the melatonin arm versus 13.298±5.119 in the placebo arm (Pvalue<0.001). The FOSQ-10 score was 24.93±5.02 in the melatonin arm versus 19.87±4.24 in the placebo arm (Pvalue= 0.006). Additionally, nighttime consequences such as sleep latency and awakenings showed significant improvement in the melatonin arm. PAP devices results revealed improvement in duration of PAP use overnight.  Conclusions Administering melatonin has been shown to improve self-reported sleep quality and PAP adherence in patients with COMISA. Trial registration Registration number IRCT20220105053635N1 was issued by the Iranian Registry of Clinical Trials (IRCT).